A Study of Socio-Demographic and Attitudinal Factors on Consumer Behavior by Individual Investors in the Indian Context - Gautam, Shalini; Matta, Mitu (Indian Journal of Finance, 2016)
Purpose: The purpose of the present paper was to study the socio-demographic and attitudinal factors of consumer behavior in the Indian context. Design/Methodology/Approach: A sample of 332 individuals was considered for the study. Various socio-demographic and attitude factors were considered to find out their association with financial behavior. Regression analysis was done on these factors against financial behavior. Findings: The results of the research showed that age, marital status, household annual income, ownership of real estate, duration of investments, and frequency of review of portfolio are the most significant socio-demographic factors that determined financial behavior. The most important attitudinal factors that determined financial behavior are interest in financial matters and tendency towards savings. Practical Implications : The disposable income of an average household has increased in the past decade or so. An average household now requires professional advice to manage its funds. This has led to an increase in competition in the financial sector for acquiring individual investors/ customers. A financial institution would always like to know who its target customer is so that it can it can focus its energies towards its target customer only. This study would help in identifying the factors an institution can look at while designing its acquisition strategies. Originality/Value : Though various studies have been done to understand consumer behavior in financial services globally, not much has been done in the Indian context. The various studies that have been conducted in the Indian context have looked at the individual factors like demography and attitude. The present study is an attempt to fill this important gap in literature and looked at both these factors cohesively.